Veil Of Shadows: Warriors: The Broken Code # 3 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2020)
"With an impostor leading ThunderClan, threatening to exile any cats who challenge him, a small but growing group of cats must find a way to expose the truth and return ThunderClan's rightful leader-before the tensions among the Clans erupt into war"--.
Ages 8-12.
Grades 4-6.
Keywords: Fantasy; Cats -- Fiction